1985
DOI: 10.1159/000299006
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans’ Cells in Squamous Metaplasia of the Human Uterine Cervix

Abstract: The number and shape of Langerhans’ cells (LC) were studied by determining cytoplasmic formaldehyde-resistant ATPase activity in whole mounts of normal and meta-plastic human cervical epithelium. In normal epithelium the number of LC per square millimeter was 52.75 ± 2.21. A similar number was found in completely differentiated metaplastic squamous epithelium (49.11 ± 2.42), but their shape was different with less branching processes. When metaplasia was still incomplete, and numerous mucous cells remained, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…We also noted a significant decrease in the density of S100-positive Langerhans' cells in metaplastic epithelium compared with normal exocervical tissue. The reduction of Langerhans' cells in immature metaplasia has already been reported [30] and it has been suggested that the presence of glandular columnar cells provides some kind of negative chemotactic stimulus which prevents migration of Langerhans' cells into metaplastic epithelium [30]. The density of Langerhans' cells detected by anti-S100 antibody in the present study was similar to that previously reported with other antibodies, such as anti-CDla, in normal and pathological cervical tissues [51 ].…”
Section: Discussionsupporting
confidence: 90%
“…We also noted a significant decrease in the density of S100-positive Langerhans' cells in metaplastic epithelium compared with normal exocervical tissue. The reduction of Langerhans' cells in immature metaplasia has already been reported [30] and it has been suggested that the presence of glandular columnar cells provides some kind of negative chemotactic stimulus which prevents migration of Langerhans' cells into metaplastic epithelium [30]. The density of Langerhans' cells detected by anti-S100 antibody in the present study was similar to that previously reported with other antibodies, such as anti-CDla, in normal and pathological cervical tissues [51 ].…”
Section: Discussionsupporting
confidence: 90%
“…41 The anatomical localization of the immune response has also been shown to be an important factor in the TH1/TH2 decision. 42 This is emphasized by the observation, in this study as well as in previous reports, 35,43 of a decreased density of Langerhans' cells in normal cervical tissues showing squamous metaplasia, compared with ectocervical epithelium. It has been suggested that the presence of glandular columnar cells provides some kind of negative chemotactic stimulus which prevents migration of Langerhans' cells into metaplastic epithelium.…”
Section: Discussionsupporting
confidence: 76%
“…It has been suggested that the presence of glandular columnar cells provides some kind of negative chemotactic stimulus which prevents migration of Langerhans' cells into metaplastic epithelium. 43 Another possibility is that there is a decreased production of chemoattractant molecules for Langerhans' cells in the metaplastic epithelium compared with the ectocervical squamous mucosa. The transformation zone of the cervix, where squamous metaplasia occurs, might thus be at greater risk of developing SILs not only because of mechanical factors allowing an easier entry of HPV particles into the basal cell of the metaplastic epithelium, but perhaps also because of the immunological status of this region which is already characterized, in the absence of HPV infection, by a reduced number of Langerhans' cells which have a professional APC function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a diminished density of Langerhans cells (LCs) in the transformation zone of the cervix 5,47,48 and in most cervical SILs 49,50 compared with the normal squamous mucosa. Qualitative alterations of LCs have also been reported in SILs.…”
Section: Discussionmentioning
confidence: 99%